Reação emocional do professor na relação com o aluno com deficiência - Artioli, Ana Lucia (2008)
Including students with deficiency in common class is a national education tendency aided legally and thoroughly discussed in the academic middle, but with difficulties for its accomplishment. Concerned about the educators' formation and informed that the affectivity is present and it influences the teacher-student relationship, the present study, that was developed in a social and historical perspective, aimed to know and to analyze the teachers' emotional reaction on and in the students' presence with deficiency included in common classes of state regular schools in the city of Cuiabá-MT. We selected four teachers of three schools through the application of the Adorno´s F scale and collaborators and Crochik´s P scale, being two with the largest and two with the smallest degrees of prejudice manifestation. We accomplished observation in classroom and interview with four pairs of teachers and the students indicated for them wit h deficiency: P1 had a student with physical deficiency (A1), P2 blind student (A2), P3 two blind students (A3 and A4) and P4 two deaf students (A5 and A6). The results indicated significant difference among the teachers with larger prejudice (P1 and P2) when compared with the one of smaller prejudice manifestation (P3 and P4). In that way, the teacher's affectivity should be contemplated in the discussion of the pedagogic planning of the school, in the continuous education and in the educators' formation, due to the importance for the teaching-learning process for the teacher-student relationship with deficiency or not